Feminist filter bubbles: ambivalence, vigilance and labour. Issue 15 (18th November 2021) - Kanai, Akane; McGrane, Caitlin
ABSTRACT: In this paper, we complicate and bring a new perspective to debates on the democratic limitations of filter bubbles, by exploring the case study of feminist filter bubbles. We extend understandings of the filter bubble to examine the highly reflexive, everyday ways in which filtering is adopted as a practical response to the information saturation and the politicised vulnerability engendered by digital environments. In doing so, we make a case for the necessity of filtering practices to create 'safe spaces' for feminist deliberation, at the same time as questioning whether absolute 'safety' is possible in feminist politics. Drawing on two separate studies of young feminist women who regularly engage with feminist private groups on Facebook, we document significant ambivalence regarding these closed spaces. While feminist filter bubbles were essential for surviving the risks of more open online environments, participants reported complicated feelings of guilt in not moving beyond these bubbles. Maintaining the 'safety' of these spaces also involved significant, ongoing labour in the requirement for participants to customise content within these bubbles, involving vigilant practices of moderation of content and the consistent application of trigger warnings. As such, we question whether the model of the feminist filter bubble is sustainable in the labour it requires already exhausted feminists to perform, and politically capacious enough to allow sustained difficult conversations. We suggest further critical engagement is required to connect filter bubbles to the everyday, affective politics of deliberation on social media platforms.